Mechanisms of gut homeostasis regulating Th17/Treg cell balance in PMOP - Qi, Peng; Xie, Ruixuan; Liu, Hao; Zhang, Zixuan; Cheng, Yuan; Ma, Jilong; Wan, Kangwei; Xie, XingWen (Frontiers in Immunology, 2024)
Postmenopausal osteoporosis (PMOP) is a metabolic bone disease driven by estrogen deficiency, primarily manifesting as reduced bone mass and heightened fracture risk. Its development is intricately linked to the balance between Th17 and Treg cells. Recent studies have highlighted the significant role of gut homeostasis in PMOP. The gut microbiota profoundly impacts bone health by modulating the host’s immune system, metabolic pathways, and endocrine functions. In particular, the regulation of Th17 and Treg cell balance by gut homeostasis plays a pivotal role in the onset and progression of PMOP. Th17 cells secrete pro-inflammatory cytokines that stimulate osteoclast activity, accelerating bone resorption, while Treg cells counteract this process through anti-inflammatory mechanisms, preserving bone mass. The gut microbiota and its metabolites can influence Th17/Treg equilibrium, thereby modulating bone metabolism. Furthermore, the integrity of the gut barrier is critical for systemic immune stability, and its disruption can lead to immune dysregulation and metabolic imbalances. Thus, targeting gut homeostasis to restore Th17/Treg balance offers a novel therapeutic avenue for the prevention and treatment of PMOP.